2017
DOI: 10.1021/acs.jpcc.6b12431
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CO2Chemisorption in Li5FeO4, a New High Temperature CO2Captor Material. Effect of the CO2and O2Partial Pressures

Abstract: Pentalithium ferrite (Li 5 FeO 4 ) was tested as possible CO 2 captor, both by theoretical calculations and experimental measurements. The pristine Li 5 FeO 4 compound with orthorhombic structure was synthesized via solid-state reaction and it was structural and microstructurally characterized. Later, sample was heat-treated at temperatures from room temperature to 900 °C under different CO 2 or CO 2 −O 2 atmospheres. Li 5 FeO 4 exhibits excellent CO 2 chemisorption abilities with a capture capacity about 12.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…4 Alternative approaches involve developing intermediate-temperature and high-temperature sorbents, which can directly trap CO from hot flue gases, and thus reduce the cost of CO 2 capture to more commercially acceptable levels. 5 Numerous types of sorbents including hydrotalcites 6,7 , calcium oxides [8][9][10][11] , and ceramic materials [12][13][14][15] have been studied. Calcium oxides in the form of calcium looping (CL) technology are considered to be one of the most promising candidates among these materials owing to (i) abundant naturally occurring CaO precursors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…4 Alternative approaches involve developing intermediate-temperature and high-temperature sorbents, which can directly trap CO from hot flue gases, and thus reduce the cost of CO 2 capture to more commercially acceptable levels. 5 Numerous types of sorbents including hydrotalcites 6,7 , calcium oxides [8][9][10][11] , and ceramic materials [12][13][14][15] have been studied. Calcium oxides in the form of calcium looping (CL) technology are considered to be one of the most promising candidates among these materials owing to (i) abundant naturally occurring CaO precursors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similar work has been performed with Li5AlO4, Li2CuO2 and Li5FeO4. 167,170,177 Similar to the thermodynamic oxygen addition effect, different studies have shown that water vapor addition (H2O(v)) modified the CO2 sorption process on lithium ceramics (Li2SiO3, Li4SiO4, Li2CuO2, Li2ZrO3 and Li5AlO4), mainly at low temperatures (T < 100 °C). 128,[183][184][185][186] All these studies show that H2O(v) becomes an active intermediate specie during the CO2 sorption, as it is represented in reaction (16), where Li2CuO2 is used as a lithium ceramic example.…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…It is clear from the TGA ramp experiments that Li 6 MnO 4 and Li 6 ZnO 4 exhibit a two-stage carbonation behaviour, commonly observed in other materials with a similar chemical composition and structure such as Li 5 AlO 4 , Li 5 FeO 4 , and Li 6 CoO 4 . 11,13,15 This two-stage carbonation features the onset of a small initial mass gain at low temperature around ∼600 K followed by a sharp onset and substantial mass gain initiated between 850 K and 900 K. The low-temperature regime is ascribed to reactions near the surface, whereas the high sorption of CO 2 in the high-temperature regime is ascribed to bulk solid-state reaction, enabled by a sufficiently high rate of ionic transport activated at higher temperatures.…”
Section: B Initial Carbonation Reaction Thermogravimetrymentioning
confidence: 99%